Solid-state studies of the crystalline/amorphous character in linear poly (ethylenimine hydrochloride) (PEI·HCl) polymers and their copper Complexes - Lazaro Martinez, Juan Manuel (2015)
Linear poly(ethylenimine hydrochloride) (PEI·HCl) polymers with different molecular weights (22, 87, and 217 kDa) and their copper complexes (Cu-PEI) were studied with particular attention to the crystalline/amorphous character of the polymeric chains in lyophilized and crystallized samples by using 1D and 2D solid-state nuclear magnetic resonance, X-ray photoelectron spectroscopy, and X-ray diffraction techniques. Different 13C{1H} cross-polarization and magic angle spinning experiments using delayed contact time, 1H dipolar filter and 1H spin-lock filter were crucial to determine the different mobility domains in the crystallized and lyophilized samples of PEI·HCl and Cu-PEI. 13C direct polarization experiments allowed the quantification of the crystalline/amorphous segments in each sample. The lyophilization process produced an increase in the amorphous fraction, even when some ordered domains were present, whereas the coordination of copper/sulfate ions produced a significant decrease in the mobility of polymer chains, leading to homogeneous and ordered materials even when Cu was desorbed.